Hypertension Factors Analysis of the Denkeslap Kesdam V/Brawijaya Malang - Endri Mustofa (Journal for Quality in Public Health, 2020)
Hypertension is a degenerative disease which is a serious problem nowadays. Hypertension is categorized as the silent disease or the silent killer because the sufferer does not know he has hypertension or does not know before checking his blood pressure. The aim of this study was to find out the factors that affected hypertension of the Indonesian Army, Denkeslap Kesdam V / Brawijaya Malang. The research was conducted on 11-14 November 2018 at DENKESLAP Kesdam V / Brawijaya Malang, Observational study design with cross sectional approach. The total population is 65 people and a sample of 56 people with a random sampling technique. Data collection of independent variables and dependent variables by means of observations and questionnaires. Data analysis using logistic regression test. Based on the results of the logistic regression test, the stress variable p value is 0.027; anxiety 0.033 and sleep pattern 0.39 at α: 0.05, the incidence of hypertension is significantly affected by stress, anxiety and sleep patterns. The dominant factors affecting hypertension are stress. Stress is a condition or condition of the body that is disturbed due to psychological stress. The relationship between stress and the incidence of hypertension occurs through sympathetic nerve activity. Increased nerves can increase blood pressure intermittently (erratic). So that prolonged stress can result in high sedentary blood pressure. Stress will increase peripheral vascular resistance and cardiac output so it will stimulate sympathetic nerve activity. Soldiers are advised to adopt a healthy lifestyle, exercise and maintain a diet, avoiding things that can become stressors so as to minimize hypertension